Tahap amalan kepimpinan transformasional dalam kalangan Guru Besar di Sekolah Jenis Kebangsaan Tamil, daerah Segamat - Marimuthu, Malarvily (2012)
This study was conducted to determine the level of transformational leadership among headmasters in two zones, namely Tenang Zone and the Zone of Chaah-Bekok, Segamat district in Johor. This is based on 4 aspects of 4i–Ideal Influence, Individual Consideration, Intellectual Stimulation and Inspirational Motivation. Sampling study involves 72 teachers from these zones. The survey method used in conducting the study and the data were obtained using questionnaires. Instruments used in this study are Multifactor Leadership Questionnaires (MLQ). Cronbach alpha reliability value of .9575 were obtained from the pilot study of 30 teachers. Software Statistical Package of Social Science (SPSS) 17 is used to analyze the questionnaire data in terms of frequency, mean, percentage, standard deviation, t-test and one way ANOVA. The results showed that the level of transformational leadership practices of teachers from Tenang Zone and Chaah- Bekok Zone, District Kite is high and all the dimensions of transformational leadership studied also showed higher mean values. The results showed that there are no differences in the perception of transformational leadership is a significant practice among teachers based on gender, age, and teaching experience but there are significant differences based on ethnic respondents.